Environmental Investigations and Tissue Bioaccumulation of Heavy Metals in Grey Mullet from the Black Sea (Bulgaria) and the Ionian Sea (Italy) - Fazio, Francesco; D’Iglio, Claudio; Capillo, Gioele; Saoca, Concetta; Peycheva, Katya; Piccione, Giuseppe; Makedonski, Lubomir (Animals (Basel), 2020)
The environmental monitoring of chemical toxicants has been a widely studied topic in the last few decades. The main aim of the present study was to determine the total concentration of nine elements (Cd, Cr, Pb, Ni, Al, Cu, Fe, Mn, and Zn) in the fish species grey mullet (M. cephalus) and in the coastal marine waters collected from various sampling points along the Black Sea (Bulgaria) and the Ionian Sea (Italy). Further, those results were applied to predict the pollution degree in those coastal marine environments. The fish samples were subject to acid digestion followed by appropriate analytical determination. The metal concentrations in marine water samples collected from the Black Sea (Bulgaria) and the Ionian Sea (Italy) were also analyzed. Unpaired Student’s t-test and the one-way ANOVA were applied for the statistical analysis of the data. The statistical results revealed a significant variation (p < 0.0001) in the concentration of various fish tissues. The accumulation of toxic and essential elements differs significantly in grey mullet species caught from the Black Sea (Bulgaria) and the Ionian Sea (Italy). The results from this study may serve as a convenient approach during marine pollution programs set by both countries (Italy and Bulgaria).